CAUSES AND OUTCOME OF PLEURAL EFFUSION IN CHILDREN IN A TERTIARY CARE HOSPITAL OF PESHAWAR, PAKISTAN - Iqbal, Zafar; Khan, Sher Ali; Ullah, Zia; Alam, Jamshed; Umar, Muhammad; Khan, Mohammad Yousaf (Journal of Postgraduate Medical Institute, 2019)
Objective: To determine the causes and outcome of pleural effusion in children presenting to a tertiary care hospital. Methodology: This cross sectional study was carried out in Department of Pulmonology, Lady Reading Hospital, Peshawar from August 2017 to August 2018. All the patients with age less than 15 years and having unilateral or bilateral pleural effusion were included in the study. All the children were assessed for the causes of pleural effusion. Pleural tap was performed and pleural fluid was sent for biochemical examination to determine whether the fluid was exudative or transudative. Pleural fluid was also sent for microbiological and cytological examination where, tuberculosis, other infection or malignancy was suspected.Data were recorded and analyzed using SPSS version 20. Result: Total 82 cases of pleural effusion were enrolled of whom 51 (62.1%) were males. Pleural effusion was exudative in 67 (81.7%) cases while transudative in 15 (18.3%) cases. The most frequent cause of pleural effusion was parapneumonic effusion (60.9%) followed by congestive cardiac failure (15.8%), malignancy (8.5%), tuberculosis (4.8%), renal disease (2.4%) while (7.3%) cases remained undiagnosed. Regarding outcome, among 50 patients with parapneumonic effusion, 48 cases underwent tube thoracostomy, of which 36 cases received intrapleural streptokinase (SK). Among these 36 cases, 24 cases responded to SK while 12 cases underwent decortication. Conclusion: Parapneumonic effusion is the most common cause of pleural effusion in children. Intra-pleural SK has good results in children and save many patients from surgery.